Psychotropic medication use and risks of kidney injury and fall-related events: a propensity score–matched cohort study - Wu, Yu-Hsien; Tsai, Shang-Feng; Huang, Shiau-Shian; Hou, Po-Hsun (Frontiers in Pharmacology, 2026)
BackgroundPsychotropic medications are widely prescribed, yet their long-term renal and injury-related safety in real-world populations remains incompletely defined. We examined the associations between psychotropic medication use and long-term risks of kidney injury and fall-related adverse events.MethodsWe conducted a retrospective propensity score–matched cohort study using the TriNetX global federated health research network. Adults aged ≥18 years with continuous psychotropic medication use were matched 1:1 to nonusers. Primary outcomes were 5-year acute kidney injury (AKI) and chronic kidney disease (CKD). Secondary outcomes included falls, fractures, head injury, dizziness or vertigo, and rhabdomyolysis. Relative risks (RRs) and 95% confidence intervals (CIs) were estimated.ResultsAmong 169,309 matched pairs (mean age 47 years; 69% female), psychotropic medication use was associated with higher 5-year risks of AKI (2.85% vs. 1.55%; RR 1.83, 95% CI 1.75–1.92), incident CKD stage 3 (7.50% vs. 6.18%; RR 1.21, 95% CI 1.18–1.25), and advanced CKD (1.13% vs. 0.88%; RR 1.28, 95% CI 1.20–1.37). Increased risks were also observed for fall-related outcomes, including falls (RR 2.32), fractures (RR 1.85), head injury (RR 1.88), dizziness or vertigo (RR 1.81), and rhabdomyolysis (RR 3.71). Associations were generally consistent across medication classes, age groups, and sex.ConclusionPsychotropic medication use was associated with modest but significantly higher long-term risks of kidney injury and fall-related events in a large real-world cohort, even after accounting for underlying psychiatric and neurologic conditions. These findings support the need for integrated renal monitoring and injury-prevention strategies in patients receiving long-term psychotropic therapy.